Tackling illegal activities through tax law: Al Capone case study - Matej Kačaljak (DANUBE: Law, Economics and Social Issues Review, 2015)
This paper discusses the Al Capone case and identifies legal institutions which contributed to the conviction of Al Capone for tax evasion in the USA and discusses similarities in Slovak law. The Slovak legal environment is assessed with the aim of identifying potential room for improvement. Under an assumption of identical factual circumstances, it is tested whether Al Capone would be convicted of tax evasion in the Slovak Republic and if not, what would be the main reasons. The paper concludes that due to some, probably unintentional, specifics of Slovak tax and criminal law, Al Capone could not be convicted of tax evasion by the Slovak courts. In our opinion, these specifics do not, however, constitute material elements of the basic structure of Slovak tax and criminal law and could be relatively easily corrected.
Keywords: 330; Personal Income Tax; Tax Evasion; Net Worth Method; Al Capone; Slovak Republic